Bewertung des Potentiales der Elektrobenetzung für Trennkolonnen - Dechert, Christopher; Riese, Julia

Die LIFT: Lernwerkstatt Inklusion und individuelle Förderung am Technologiepark der Universität Paderborn - Ellersiek, Annchristin; Kottmann, Brigitte; Möbius, Henning; Timmermanns, Franziska; Wapelhorst, Jule (Atlas der Hochschullernwerkstätten. Ein (un-)vollständiges Kompendium.)

Die Lernwerkstatt an der Universität Bielefeld: Ein gemeinsamer Ort, ein Ort für gemeinsames Lernen - Kottmann, Brigitte; Stets, Mona (Atlas der Hochschullernwerkstätten. Ein (Un-)vollständiges Kompendium.)

A novel welding schedule for expanding the expulsion-free process window in resistance spot welding of dissimilar joints with ultra-high strength steel - Yang, Keke; Wang, Zhuoqun; Haak, Viktor; Olfert, Viktoria; El-Sari, Bassel; Hein, David; Biegler, Max; Rethmeier, Michael; Meschut, Gerson (Journal of Manufacturing Processes)

Philosophy’s 25-Years Principle: Philosophy between Intuitive Understanding and Discursive Reasoning - Milkov, Nikolay (Journal of Research in Philosophy and History)
The present paper has two objectives. First, it explicates the story, initially portrayed by Eckart Förster, that philosophy allegedly started with publishing of Kant’s CPR and ended a quarter century later when Hegel’s Phenomenology of Mind appeared. We address the questions in what sense this happened and how is this development to be interpreted? Secondly, we demonstrate that similar radical transition from new, “true” beginning of philosophy to its apparent finishing took place in two other, high profile occasions in the history of Western philosophy, in two key points of its development: in the years 390-365 bc, between the early and the late Plato, and between 1898 and 1922, between Russell and Wittgenstein’s Tractatus. These three short-lived, spectacular transitions from philosophy’s alleged start to its alleged ultimate accomplishment give us good reason to speak about a specific 25-years principle in philosophy. In a peculiar way, this principle reveals philosophy’s true nature.
Keywords: Aristotle; Hegel; Kant; Plato; Russell; Wittgenstein

Fractional Variational Integrators Based on Convolution Quadrature - Hariz Belgacem, Khaled; Jiménez, Fernando; Ober-Blöbaum, Sina (Journal of Nonlinear Science)
Abstract Fractional dissipation is a powerful tool to study nonlocal physical phenomena such as damping models. The design of geometric, in particular, variational integrators for the numerical simulation of such systems relies on a variational formulation of the model. In Jiménez and Ober-Blöbaum (J Nonlinear Sci 31:46, 2021), a new approach is proposed to deal with dissipative systems including fractionally damped systems in a variational way for both, the continuous and discrete setting. It is based on the doubling of variables and their fractional derivatives. The aim of this work is to derive higher-order fractional variational integrators by means of convolution quadrature (CQ) based on backward difference formulas. We then provide numerical methods that are of order 2 improving a previous result in Jiménez and Ober-Blöbaum (J Nonlinear Sci 31:46, 2021). The convergence properties of the fractional variational integrators and saturation effects due to the approximation of the fractional derivatives by CQ are studied numerically.

Received and Perceived Peer Acceptance in Relation to Enjoyment, Social Competence, and Physical Activity in Primary School Physical Education and the Role of Peer-Relatedness Need Satisfaction - de Bruijn, Anne G.M.; Grimminger-Seidensticker, Elke (Journal of Teaching in Physical Education)

Susan Stebbing and Some Poorly Explored Venues of Analytic Philosophy - Milkov, Nikolay (Susan Stebbing: Analysis, Common Sense, and Public Philosophy)

Wisdom's Wittgenstein - Milkov, Nikolay (Wittgenstein and Other Philosophers: His Influence on Historical and Contemporary Analytic Philosophers, 2 vol., Volume II)
In 1921, John Wisdom (1904–1993) became a member of Fitzwilliam House, Cambridge, where he read philosophy and attended lectures by G. E. Moore, C. D. Broad, and J. E. McTaggart. He received his BA in 1924, after which he worked for five years at the National Institute of Industrial Psychology. From 1929 to 1934, Wisdom was a Lecturer in the department of logic and metaphysics at the University of St Andrews and a colleague of G. F. Stout. After the publication of his book Interpretation and Analysis (1931) and five articles on “Logical Constructions” in Mind (1931–3), Wisdom became a Lecturer in Moral Sciences in Cambridge and a Fellow of Trinity College. This gave him the opportunity to gain first-hand knowledge of Wittgenstein’s philosophy. Since nothing by Wittgenstein but Tractatus appeared in print for decades, Wisdom’s publications of these years were—mistakenly—read as portents of the new ideas of Wittgenstein himself. The publication of Wittgenstein’s Philosophical Investigations in 1953 brought with it, among other things, the fall of Wisdom’s popularity.
Keywords: elucidation; facts; Frege; language; metaphysics; G. E. Moore; Russell; Stebbing; John Wisdom; Wittgenstein

Stebbing's Wittgenstein - Milkov, Nikolay (Wittgenstein and Other Philosophers: His Influence on Historical and Contemporary Analytic Philosophers, vol. II)
Susan Stebbing wrote only once on Wittgenstein, in her paper ‘Logical Positivism and Analysis’ (1933). The paper was unusually critical of Wittgenstein. It put the Cambridge analytic philosophy of Moore and Russell in a sharp opposition to the positivist philosophy of the Vienna Circle, in which Stebbing included Wittgenstein. Whereas the positivists were interested in analysing language, the Cambridge realists were analysing facts. To be more explicit, the analytic philosophers were engaged in directional analysis, which seeks to illuminate (to elucidate) the multiplicity of the analysed facts. In contrast, positivists aimed at a final analysis that proves that there are simples. Stebbing’s sympathies were clearly on the side of the Cambridge realists. The important implication of Stebbing’s paper was that it urged Wittgenstein to change the style of his philosophy, abandoning those points which allegedly connected him with the Vienna Circle.
Keywords: directional analysis; elucidation; facts; metaphysics; G. E. Moore; Russell; Stebbing; John Wisdom; Wittgenstein

Integrating Practice-Based Learning into Formal Education: Stakeholder Perspectives on the Challenges of Learning Location Cooperation (LLC) in Germany’s Dual VET System - Schwede, Jana; Heisler, Dietmar; Harteis, Christian (Social Sciences)

Der König lädt ein oder: zivilisierte Kontakte im Premier Versailles (Les Plaisirs de l'île enchantée / La princesse d'Élide) - Steigerwald, Jörn ((Kon-)Figurationen des Kontakts Transfer, Berührung und Alterität in den romanischen Literaturen der Frühen Neuzeit)

Leveraging Self-Adaptive Systems and Generative AI for Personalizing Educational Serious Games: Architecture and Future Challenges - Bucchiarone, Antonio; Bonetti, Federico; Yigitbas, Enes (Proceedings of the 20th International Conference on Software Engineering for Adaptive and Self-Managing Systems (SEAMS 2025))

Seamless Augmented Reality Support for a Computer-Assisted Surgery System for Minimally Invasive Orthopedic Surgeries - Schlenker, Julian; Vater, Hendrik; Yigitbas, Enes; Dann, Alexander (Proceedings of the 27th International Conference on Human-Computer Interaction (HCII 2025))

Taxonomy and Analysis of Security Vulnerabilities, Privacy Violations and Potential Mitigation Strategies to XR Systems - Schmidt, Leonard; Yigitbas, Enes (Proceedings of the 18th International Conference on PErvasive Technologies Related to Assistive Environments (PETRA 2025))

Immersive Smart Home Planning and Automation with Mixed Reality and Digital Twin Technologies - Yigitbas, Enes; Karch, Julian (Proceedings of the 18th International Conference on PErvasive Technologies Related to Assistive Environments (PETRA 2025))

Augmented Reality-Assisted Assessment of Workplace Ergonomy - Yigitbas, Enes; Karch, Julian (Proceedings of the 18th International Conference on PErvasive Technologies Related to Assistive Environments (PETRA 2025))

Blackbox Unit Testing of Virtual Reality Applications - Geil, Manuel; Wübbeke, Andreas; Yigitbas, Enes (Proceedings of the 27th International Conference on Human-Computer Interaction (HCII 2025))

Monitoring phage infection and lysis of surface-immobilized bacteria by QCM-D - Pothineni, Bhanu K.; Probst, René; Kiefer, Dorothee; Dobretzberger, Verena; Barišić, Ivan; Grundmeier, Guido; Keller, Adrian (Analytical and Bioanalytical Chemistry)
Abstract While being a promising approach for the treatment of infections caused by drug-resistant, pathogenic bacteria, the clinical implementation of phage therapy still faces several challenges. One of these challenges lies in the high strain-specificity of most bacteriophages, which makes it necessary to screen large phage collections against the target pathogens in order to identify suitable candidates for the formulations of personalized therapeutic phage cocktails. In this work, we evaluate the potential of quartz crystal microbalance with dissipation monitoring (QCM-D) to identify and detect phage infection and subsequent lysis of bacteria immobilized on the surfaces of the QCM-D sensors. Using lytic Escherichia coli phage T7 as a model, we show that phage infection of E. coli cells results in various unique alterations in the behaviors of the frequency (Δ f ) and dissipation (Δ D ) signals, which are not observed during exposure of the E. coli strain to non-infectious Bacillus subtilis phage phi29 at similar concentration. To aid future phage screening campaigns, we furthermore identify a single measurement parameter, i.e., the spread between the different overtones of Δ D , that can be used to detect phage-induced lysis. For T7 infection of E. coli , this is achieved within 4 h after inoculation, including immobilization and growth of the bacteria on the sensor surface, as well as the completed phage propagation cycle. Given the commercial availability of highly automated multichannel systems and the fact that this approach does not require any sensor modifications, QCM-D has the potential to become a valuable tool for screening medium-sized phage collections against target pathogens. Graphical Abstract

Counting two-step nilpotent wildly ramified extensions of function fields - Gundlach, Fabian; Seguin, Beranger Fabrice (arXiv:2502.18207)
We study the asymptotic distribution of wildly ramified extensions of function fields in characteristic $p > 2$, focusing on (certain) $p$-groups of nilpotency class at most $2$. Rather than the discriminant, we count extensions according to an invariant describing the last jump in the ramification filtration at each place. We prove a local-global principle relating the distribution of extensions over global function fields to their distribution over local fields, leading to an asymptotic formula for the number of extensions with a given global last-jump invariant. A key ingredient is Abrashkin's nilpotent Artin-Schreier theory, which lets us parametrize extensions and obtain bounds on the ramification of local extensions by estimating the number of solutions to certain polynomial equations over finite fields.